Effectiveness of the California Mastitis Test (CMT), Reductase Test, and Alcohol Test for Dairy Cows Subclinical Mastitis Detection - Eriza Rosalina Rochmah; Dadik Raharjo; Sri Hidanah; Mustofa Helmi Effendi; Adiana Mutamsari Witaningrum; Sunaryo Hadi Warsito (Universitas Airlangga, 2023)
Mastitis is an inflammation of the mammary glands caused by pathogenic bacteria Mastitis divided into 2 types, clinical mastitis which has symptoms of swelling and changes in the shape of the mammary gland, while subclinical mastitis does not indicate clear symptoms. Subclinical mastitis is a very high case in Indonesia, around 97-98%, while clinical mastitis is 2-3%. Effectiveness of the california mastitis test (CMT), reductase test and alcohol test to detect subclinical mastitis in dairy cattle. The number of samples taken was 60 samples of fresh dairy milk from 15 cattles in Medowo Village as much as 50 ml for each sample. The results showed that the test was very effective in identifying subclinical mastitis in dairy cattle. 15% positive results were obtained for subclinical mastitis using CMT, 10% of the milk quality was not good during the reductase test and 18.33% positive with the alcohol test from a total of 60 samples obtained.